Meningkatkan Kemampuan Mengenal Huruf Konsonan Melalui Penggunaan Media Big Book Pada Anak Tunagrhita Ringan - Nafami Kartika; Asep Ahmad Sopandi (Jurnal Penelitian Pendidikan Khusus, 2023)
This research was motivated by the problems found in SLB Perwari Padang in class V mild mentally retarded children. There was one child who had problems recognizing consonants. So far, teachers teach children by means of demonstrations and lecture methods, and the lack of interest in children in the learning process in the introduction of less diverse consonants that will be explained to children. To overcome this problem, the researcher aims to improve children's ability to recognize consonants through big book.The research method used is classroom action research which consists of two cycles. Each cycle consists of four face-to-face meetings and each lesson is evaluated. The cycle is carried out in several stages, namely, planning, implementing actions, observing, and.reflectingData collection techniques used are observation, documentation, and tests.The results showed that: 1) the learning process to recognize consonants for mild mentally retarded children was carried out using big book media. 2) the ability to recognize consonants for mild mentally retarded children in grade V was increased using big book. This can be seen from the data before the child's ability to act in the 24 N indicators of consonant letter recognition (16.66%). Meanwhile, at the end of the first cycle, the ability of N increased (62.5%). In the second cycle the ability of N increased (85.41). So it can be concluded that the use of big book media can increase the ability to recognize consonants.